Preparation of Organic Scintillators and Applications in Neutron-Gamma Discrimination - Lichuan, Qin; Peng, Wang; Haoran, Zhang; Shuqin, Wang; Wei, He; Jie, Wen (INTI International University, 2025)
Neutron detection holds significant strategic importance in fields such as nuclear safety, medicine, and high-energy physics. However, it is often compromised by gamma-ray interference, making efficient discrimination technology a critical challenge. Organic scintillators, with their advantages of high neutron detection efficiency, rapid response time, and morphological adaptability, have emerged as core materials in neutron-gamma discrimination research. This paper systematically reviews the luminescence mechanisms of organic scintillators and the principles of pulse shape discrimination (PSD). It analyzes the preparation methods, performance characteristics, and research progress of crystalline, liquid, plastic, and loaded scintillators. Case studies highlight the effective enhancement of neutron signal-to-noise ratios and imaging resolution in nuclear power plant monitoring, PET imaging, and high-energy physics experiments using organic scintillators. Future developments in organic-inorganic composite systems and novel perovskite materials are anticipated to expand the broader application of organic scintillators in neutron detection. Among these materials, perovskite-based organic scintillators exhibit the most promising application prospects in future high-precision neutron detection scenarios due to their unique combination of high crystallinity, tunable optical bandgap, and excellent radiation resistance